2015
DOI: 10.1007/s10974-015-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

From pluripotency to myogenesis: a multistep process in the dish

Abstract: Pluripotent stem cells (PSCs), such as embryonic stem cells or induced pluripotent stem cells are a promising source of cells for regenerative medicine as they can differentiate into all cell types building a mammalian body. However, protocols leading to efficient and safe in vitro generation of desired cell types must be perfected before PSCs can be used in cell therapies or tissue engineering. In vivo, i.e. in developing mouse embryo or teratoma, PSCs can differentiate into skeletal muscle, but in vitro thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 122 publications
(186 reference statements)
0
20
0
Order By: Relevance
“…However, it was previously shown that in order to induce myogenic differentiation of ESCs one has to either overexpress myogenic factors such as MyoD, Pax3 or Pax7 or treat the them with precisely designed cocktail of factors (reviewed in ref. 33). ESCs that were not subjected to such treatments fail to effectively differentiate and fuse with myoblasts most probably due to the fact that they do not initiate the expression of M-cadherin or vascular cell adhesion molecule (V-CAM1) that are also crucial for fusion 25 …”
Section: Discussionmentioning
confidence: 99%
“…However, it was previously shown that in order to induce myogenic differentiation of ESCs one has to either overexpress myogenic factors such as MyoD, Pax3 or Pax7 or treat the them with precisely designed cocktail of factors (reviewed in ref. 33). ESCs that were not subjected to such treatments fail to effectively differentiate and fuse with myoblasts most probably due to the fact that they do not initiate the expression of M-cadherin or vascular cell adhesion molecule (V-CAM1) that are also crucial for fusion 25 …”
Section: Discussionmentioning
confidence: 99%
“…The MyoD gene family (MyoD1, Myf5, MyoG, and Myf6) has been shown to act as a key regulator that controls the expression of specic proteins in the proliferation and differentiation of muscle cells. [8][9][10][11]18,27 Among them, MyoD1 plays an important role in muscle growth in the transcriptional regulation of muscle-specic genes, 38 while Myf6 (MRF4) primarily functions in a downstream role in myogenesis, including myober formation 19,39 and the maintenance of the muscle phenotype. 39 The Myf6 and MyoD1 promoters are regulated quite differently, leading to opposite roles of MRF4 and MyoD in cell proliferation and myogenic differentiation, 40 in which MyoD is a potential negative intercessor of MRF4 in regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Several transcriptional regulatory factors, including myoblast determination protein family members, are believed to act as terminal effectors of signaling cascades and to produce appropriate developmental stage-specic transcripts, regulating the development and growth of skeletal muscle. 7 Skeletal myogenesis is regulated by the MyoD protein family, which includes four myogenic regulatory factors (MRFs) [8][9][10][11] that belong to a family of muscle-specic basic helix-loop-helix (bHLH) transcription factors: myogenic differentiation (MyoD), 12 myogenic factor 5 (Myf5), 13 myogenin (MyoG), 14 and myogenic regulatory factor 4 (MRF4, also known as Mrf6). 15 Among the MRFs, the determination factor Myf5 is expressed before adoption of the myogenic fate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite cells typically express both Pax3 and Pax7, which are transcription factors that prevent satellite cells from becoming differentiated into specific myogenic cells (Swierczek et al, 2015; Wang et al, 2014). Injury can stimulate these satellite cells produce Myf5 and MyoD to initiate differentiation and produce new myofibers (Dumont et al, 2015; Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%